From Social Care to Spiritual Empowerment: Reconstructing Islamic Education for Older Adults in Welfare Institutions - Sumar; Abdurrahmansyah; Fajri Ismail; Prof Indah Wigati; Prof Ermis Suryana (Al Qodiri : Jurnal Pendidikan, Sosial dan Keagamaan, 2026)
The increasing elderly population has generated multidimensional challenges for welfare institutions, particularly in addressing the spiritual and psychosocial dimensions of ageing. While most elderly welfare institutions continue to prioritize physical care, healthcare services, and social protection, spiritual empowerment remains relatively marginalized within institutional practices. This study aimed to evaluate the implementation of Islamic educational reinforcement programs in elderly welfare institutions in Bangka Belitung Province, Indonesia, and to reconstruct Islamic education as a model of spiritual empowerment for older adults. The study employed a qualitative evaluative design using the Context, Input, Process, and Product (CIPP) evaluation framework. Data were collected through semi-structured interviews, participatory observations, and document analysis involving institutional leaders, caregivers, Islamic education facilitators, and elderly residents. The findings revealed that spiritual educational activities were generally implemented as supplementary and ritualistic programs without systematic educational orientation. The context evaluation identified unmet spiritual and psychosocial needs among elderly residents, while the input and process evaluations revealed limitations in human resources, facilities, institutional support, and elderly-centered pedagogical approaches. Nevertheless, the product evaluation demonstrated that participation in Islamic educational activities contributed positively to emotional wellbeing, social connectedness, spiritual awareness, and meaningful ageing. Based on these findings, the study proposes a reconstruction of Islamic education through reflective spiritual learning, emotional accompaniment, psychosocial integration, elderly-centered pedagogy, and institutional commitment to spiritual empowerment. The study concludes that spiritually integrated Islamic education can serve as a transformative framework for promoting holistic wellbeing, emotional resilience, and meaningful ageing among older adults in welfare institutions.